Amide‐phosphonium Salt Catalyzed Enantioselective Vinylogous Mannich Addition of Coumarins to Isatin Imines. Issue 2 (5th November 2019) - Wang, Jing; Zhang, Shuo; Ding, Weizhong; Wang, Chenghan; Chen, Jie; Cao, Weiguo; Wu, Xiaoyu
Abstract: An asymmetric vinylogous Mannich reaction between 3‐cyano‐4‐methylcoumarins and N ‐Boc isatin imines catalysed by amide phosphonium salt is described. This method allows the formation of intriguing adducts bearing both 3‐aminooxindole and coumarin moieties in excellent yields with excellent enantioselectivities. The utility of this method was illustrated by a gram scale synthesis using as low as 0.1 mol % of catalyst without chromatographic purification, and removal of the Boc protecting groups on the primary amine functionality in Mannich products. Abstract : Phosphine catalysis : Under 0.1 mol % of phosphonium salt catalyst, vinylogous Mannich reaction between 3‐cyano‐4‐methylcoumarins and N‐Boc isatin imines has been developed. This method allows the formation of intriguing adducts bearing both 3‐aminooxindole and coumarin moieties in excellent yields with excellent enantioselectivities. The utility of this method was illustrated by a gram scale synthesis without chromatographic purification, and removal of the Boc protecting groups on the primary amine functionality in Mannich products.